Nature Sunflower Stalk Pith with Zwitterionic Hydrogel Coating for Highly Efficient and Sustainable Solar Evaporation. (27th October 2021) - Su, Xin; Hao, Dezhao; Sun, Mingyue; Wei, Tingshu; Xu, Dake; Ai, Xicheng; Guo, Xinglin; Zhao, Tong; Jiang, Lei
Abstract: Solar‐driven water evaporation is considered to be an appealing way to solve water scarcity issues globally. Various natural creatures possess unique structural features and exhibit an excellent pumping ability in arid environments. Motivated by sunflower stalk pith, here, the biomass porous foam modified with zwitterionic hydrogel coating for solar desalination devices is introduced. It is demonstrated that the multi‐curvature and gradient honeycomb architecture offers a remarkable solar desalination system, which combines critical aspects of solar evaporation including high light absorption, localizing converted heat, rapid water transport, water activation, and multi‐channel release of steam via its ubiquitous structure, and substantially outperforms other natural biomass materials. The device exhibits long‐term stability in actual seawater, as well as high performance for soybean oil emulsion and oily brines (crude oil, salts). Furthermore, the long‐term use of excellent storability to prevent putrefying is shown, which is attributed to the outstanding antifouling property of zwitterionic hydrogel. It is envisioned that the nature material with the advantage of being inexpensive, environmentally friendly, and portable, may be a new candidate for water purification and desalination. Abstract : A low‐density, low thermal conductivity, environment friendly, inexpensive, efficient, and stable solar steam device is developed using sunflower pith with a zwitterionic hydrogel coating. The rapid water transport property, salt‐resistant and anti‐biofouling performance are due to synergistic effects of the multi‐curvature gradient porous structure and zwitterionic hydrogels. This natural biomass evaporator could obtain clean water from a variety of sewage.